CRITICAL REVIEW ON AGASTHYAHAREETAKI AVALEHA WITH SPECIAL REFERENCE TO SWASAHARA KARMA - V S Nithya; V.C Indulekha; S K Veena (International Journal of Ayurveda and Pharma Research, 2020)
Respiratory disorders are one of the leading causes of morbidity worldwide. In Ayurvedic classics many poly herbal preparations are mentioned for curing respiratory disorders. Agasthyahareetaki avaleha is one such formulation mentioned in classical text books specially indicated for curing Swasa, Kasa, Vishamajvara etc. A detailed literature survey has been conducted to explore the probable mode of action of Agasthyahareetaki Avaleha in Swasa Roga. Most of the ingredients are having anti asthmatic, anti-inflammatory, immune modulator and antimicrobial activities may works on respiratory pathology. Apart from this Katu, Tikta Rasa, Ruksa, Lagu Guna and Kaphavata hara, Swasa- Kasa- Sopha Hara property of ingredients will hamper the pathology of Swasaroga.